Navigating Trade Turbulence: Identifying Indonesia's Optimal Trade Partners Amid the US-China Trade War Using Relative Output, Market Potential, and Trade Openness - Said Maulana Azry; Fajri Muharja (Electronic Journal of Education, Social Economics and Technology, 2025)
This study investigates how Indonesia can identify optimal bilateral trade partners by analyzing the effects of relative output, market potential, and trade openness on its terms of trade (ToT). The analysis is timely amid escalating U.S.–China trade tensions (2024–2025), which have disrupted global supply chains and altered trade dynamics. Using panel data from 2009 to 2019, the study avoids periods of major shocks such as the 2007–2008 global financial crisis and the COVID-19 pandemic post-2020. A quasi-maximum likelihood (QML) method is employed to estimate the impact of bilateral economic fundamentals on Indonesia’s ToT, accounting for heterogeneity and endogeneity. Results show that Indonesia’s ToT improves when trading with countries that have higher relative output, expanding market potential, and greater trade openness. These findings highlight the importance of trade diversification and suggest that Indonesia should prioritize partnerships with dynamic, open economies to strengthen its resilience to global trade shocks. The study offers strategic insights for navigating a shifting international trade environment.